hns mRNA downregulates the expression of galU and attenuates the motility of Salmonella enterica serovar Typhi - Zhao, Xin; Yang, Fanfan; Wang, Yurou; Zhang, Ying (International journal of medical microbiology, 2021)
•hns mRNA is a new bifunctional RNA.•hns mRNA acts as an antisense RNA that downregulates galU expression.•GalU-3′-UTR is the target of hns mRNA.•hns mRNA attenuates the motility of S. Typhi by downregulating galU expression. Recently, multiple bifunctional RNAs have been discovered, which can both be translated into proteins and play regulatory roles. hns encodes the global gene silencing factor H-NS, which is widespread in Gram-negative bacteria. This study reported that hns mRNA of Salmonella enterica serovar Typhi (S. Typhi) was a bifunctional RNA that could act as an antisense RNA downregulating the expression of galU, the coding gene of uridine triphosphate-glucose-1-phosphate uridylyltransferase, and attenuating bacterial motility. galU, which is located at the opposite strand of hns, was identified to have a long 3′-untranslated region that overlapped with hns and could be processed to produce short RNA fragments. The overexpression of hns mRNA inhibited the expression of galU. The deletion of galU attenuated the motility of S. Typhi, while the complementation of galU nearly restored the phenotype. Overexpressing hns mRNA in the wild-type strain of S. Typhi inhibited the motility and the expression of flagellar genes, while overexpressing hns mRNA in the galU-deletion mutant did not influence bacterial motility. In conclusion, hns mRNA has been identified to be a new bifunctional RNA that attenuates the motility of S. Typhi by downregulating the expression of galU.